PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Nurul Azmi; isnurhadi isnurhadi; umar hamdan (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2018)
This research ains to test the influence of profitability, firm size on firm value with capital structure as an intervening variable. Analysis of data were did in the manufacturing companies listed on the Indonesia Stock Exchange during the period 2011-2016. The data analyzed by using multiple linear regression method. The result showed that profitability has negative and significant on capital structure, firm size has negative and significant on capital structure, profitability do not influenced on firm value, firm size do not influenced on firm value, capital structure do not influenced on firm value. Meanwhile the capital stucture can not mediate the relationship between profitability and firm size against firm value. Keywords : profitability, firm size, firm value and capital structure